Bez znieczulenia . Rough Treatment – aka Without Anesthesia - Wajda, Andrzej (Zespol Filmowe X, 1978)
Duration: 01:49:00 A famous journalist presents the powers-that-be with a problem when he displays his full political skill and knowledge on a television show. His enemies take away his privileges when he is away. The shock of being "unwanted" parallels a deeper disappointment in his private life: his wife has an affair with a jealous young rival, and after 15 years of marriage and two daughters, she wants a divorce. She offers no explanations as he tries to solve these problems himself. He takes to drinking heavily with students eager to attend his seminar after discovering the class has been canceled. A female student moves into his apartment. The journalist, once suave and commanding is reduced to silence. In a widely publicized divorce case he refuses to contest the lies presented to the court. Shortly afterwards he dies mysteriously in his apartment when the gas heater explodes. Wajda shows how the communist regime can destroy its people with no hesitation and warns that the system works without anesthesia. This message is symbolically illustrated when the journalist visits a dentist – he is offered an anesthetic, he declines, but then he faints. Many critics compared Zapasiewicz’s acclaimed performance to Kafka’s Joseph K.